Paving the way to novel phosphorus-based architectures: a noncatalyzed protocol to access six-membered heterocycles - Romero-Nieto, Carlos; López-Andarias, Alicia; Egler Lucas, Carolina; Gebert, Florian; Neus, Jens-Peter; Pilgram, Oliver (Angewandte Chemie. International edition, 2015)
Phosphorus-based heterocycles provide access to materials with properties that are inaccessible from all-carbon architectures. The unique hybridization of phosphorus gives rise to electron-accepting capacities, a large variety of coordination reactions, and the possibility of controlling the electronic properties through phosphorus postfunctionalization. Herein, we describe a new noncatalyzed synthetic protocol to prepare fused six-membered phosphorus heterocycles. In particular, we report the synthesis of novel phosphaphenalenes. These fused systems exhibit the benefits of both five- and six-membered phosphorus heterocycles and enable a series of versatile postfunctionalization reactions. This work thus opens up new horizons in the field of conjugated materials.